Assessment of Prognostic Factors in Children with Renal Tubular Acidosis Type IV Overwhelmed by Bilateral Obstructive Uropathy - Yousefichaijan, Parsa; Sharafkhah, Mojtaba (Journal of Pediatric Nephrology, 2013)
Introduction: Hyperkalemia renal tubular acidosis (type IV) occurs secondary to impaired renal responsiveness to aldosterone. This can occur chronically in infants and children with a history of obstructive uropathy. The aim of this study was to assess of prognostic factors in children RTA type IV overwhelmed by bilateral obstructive uropathy. Materials and Methods: In this study, we recruited and observed 48 male patients with both bilateral obstructive uropathy at the urinary bladder outlet and RTA type IV for two years. In this period, we registered patients’ demographic data; also, children’s growth, sonographic data, renal function tests and serum electrolytes underwent serial assessment and in if clinically indicated, the patients were treated with drugs like citrate sodium and Kay oxalate. Results: Frequent urinary tract infection (p=0.0011), abnormal <20 weeks gestation sonography results like bilateral hydronephrosis (p=0.00001), birth weight below 2500 gr (LBW) (p=0.0014), preterm delivery (p=0.001), maternal age at birth below 20 years (p=0.0018), pregnancy more than 2 times (p=0.004), admission due to respiratory problems during infancy (p=0.003) and gestational diabetes (P=0.001) were significantly associated with a poor prognosis. Conclusions: Considering the results of this study, it seems logical to consider abortion in case of renal hydronephrosis and dysplasia in gestational age below 20 weeks. Keywords: Hyperkalemia; Urologic Diseases; Renal Tubular Acidosis